Effects of visual design in beef seedstock ads on trust, credibility, and intent to seek more information - Marley, Morgan Lynn, author; Abrams, Katie, advisor; Castillo, Dani, committee member; Ahola, Jason, committee member (Colorado State University. Libraries, 2018)
This study was intended to analyze the effect of a visual design on the viewer's trust, credibility, and intent to seek more information among Angus cattle producers. To test this relationship, 561 beef producers were recruited from Angus Media subscribers. The independent variables in this study were comprised of graphic design principles – unity, emphasis, and perceptual forces. A post-test only with control group experimental design was conducted to gather experimental data. Our results show the graphic design of a beef seedstock ranch ad promoting an upcoming bull sale did not influence viewers perceptions of trust and credibility or intent to seek more information. However, one of our research questions did reveal stronger designed ads are significantly related to trust. We suggest the study results were influenced by a first impression established through the brand description presented to all treatment groups. For future studies, we recommend a replication of this study with no brand description used in the experiment. Additional studies could compare mediocre design to superb design implemented within an ad. In other areas of study, we recommend information measures and impacts of a first impression through different brand descriptions.